Compassion satisfaction and compassion fatigue among medical social workers in Korea: the role of empathy. (26th November 2019) - Yi, Jaehee; Kim, Min Ah; Choi, Kwonho; Droubay, Brian A.; Kim, Soohyun
ABSTRACT: Medical social workers are affected by their clients' suffering, which has an impact on social workers' professional quality of life. This study examined the role of empathy in relation to professional quality of life among medical social workers in South Korea. Using the Professional Quality of Life Scale and Interpersonal Reactivity Index, we found that empathic concern and personal distress were significant components of empathy and were correlated with professional quality of life. Empathic concern was positively associated with compassion satisfaction and negatively associated with burnout. Personal distress was correlated with all components of quality of life: compassion satisfaction, secondary traumatic stress, and burnout. Women had significantly higher levels of burnout than men; religious affiliation was associated with higher levels of compassion satisfaction; and longer years of employment was associated with higher levels of secondary traumatic stress. Medical social workers should be educated on and trained in how empathy can help them address compassion fatigue and promote compassion satisfaction.